Liver Stiffness, Not Fat Liver Content, Predicts the Length of QTc Interval in Patients with Chronic Liver Disease. (23rd December 2019) - Bellan, Mattia; Rigamonti, Cristina; Giacomini, Greta Maria; Makmur, Giulio; Marconi, Cecilia; Nicosia, Francesco; Panero, Antonio; De Benedittis, Carla; Burlone, Michela E.; Minisini, Rosalba; Pirisi, Mario
Abstract : The severity of fatty liver at ultrasound has been associated with QT length, a finding invoked to explain the excess cardiovascular risk of patients with fatty liver. However, the ability of ultrasound to stage accurately the severity of fatty liver is limited, with fibrosis a major confounder. Here, we aimed to verify the alleged relationship between fat liver content and QT length using a technique apt at discriminating steatosis from fibrosis noninvasively, i.e., transient elastography (TE) with measure of liver stiffness (LS) and controlled attenuation parameter (CAP). A prospectively collected derivation cohort of 349 patients with chronic liver disease (CLD) of any etiology (N = 105 with nonalcoholic fatty liver) was studied to identify clinical, laboratory, and instrumental predictors of the corrected QT interval (QTc) and QTc prolongation, including LS and CAP. The results were validated on a subgroup of patients belonging to the derivation cohort (out of sample validation), as well as on a completely different group of N = 149 subjects with CLD (out of time validation). QTc values were directly related to liver stiffness (LS; ρ = 0.137 ; p = 0.011 ), heart rate (HR; ρ = 0.307 ; p < 0.001 ), and age (ρ = 0.265 ; p < 0.001 ) and were significantly longer in females (p < 0.001 ). In contrast, QTc was not associated with the value of controlled attenuation parameter (ρ = 0.019 ; p = 0.718 ); moreover, no discernible differences in QTc length were noted based on CLD etiology. QTc was prolonged in 24/349 patients (6.9%); age, HR, and LS were independent predictors of QTc prolongation (χ 2 = 23.7, p < 0.001 ). Furthermore, QTc values (after logarithmic transformation) were predicted by a model including age, gender, HR, and LS (F = 14.1, R 2 = 0.198, p < 0.001 ). These latter results were validated by both out-of-sample and out-of-time methods. In conclusion, TE findings strongly suggest that among patients with CLD, fibrosis, not steatosis, is a major determinant of QTc length.